E-Modul Berbasis POGIL yang Inovatif dengan Integrasi MolView: Memajukan Kecerdasan Visual-Spasial dalam Pembelajaran Geometri Molekuler - Izzati, Nila Zulfa; Dwiningsih, Kusumawati (Jurnal Pendidikan dan Pengajaran, 2025)
Molecular shapes are abstract and require strong spatial visualization. This study aims to develop a MolView-based POGIL e-module that integrates active learning with 2D-to-3D interactive visualization, meeting the criteria of validity, practicality, and effectiveness in improving four indicators of visual intelligence: imagining, conceptualizing, pattern-seeking, and problem-solving in molecular shapes. This study employs the RnD method with the 4D approach (define, design, develop, and dissect) but is limited to the development stage. The study subjects were 36 high school students. Data collection techniques include sheets, visual intelligence tests, cognitive ability tests, observation sheets, and student response questionnaires. Data analysis techniques use the N-Gain Score test and the Wilcoxon Signed-Rank Test. The results of the validity of content, construction, and visual intelligence with a median of 3 with a valid category. As many as 88.8% of students achieved high improvement, and the Wilcoxon Test showed sig. 0.000 <0.05, so that the e-module is included in the effective category. The percentage of student response questionnaires was 96.11%, while the percentage of relevant activities during learning reached 94.65%, which fell within the practice category. Thus, the findings obtained were interactive e-modules based on POGIL that met the criteria of validity, practicality, and effectiveness in improving students' visual intelligence on molecular form material.